PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS 1 PALEMBANG - Qatrunnada Ramadhania; Kusmiyanti Kusmiyanti (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This research aims to acknowledge how much work motivation influences employee performance in Lembaga Pembinaan Khusus Anak (LPKA) Class 1 Palembang. Research methods are classified into quantitative research. The population used in this research are the 75 employees of Lembaga Pembinaan Khusus Anak (LPKA) Class 1 Palembang. The sample was taken by applying a saturated sampling technique, in which everyone is sampled. The amount of samples is 75 people. The finding shows that there is a positive and significant influence of work motivations on employee performance in Lembaga Pembinaan Khusus Anak (LPKA) Class 1 Palembang. It can be concluded that the work motivation variable (X) gives a real impact on the employee performance variable (Y) because of the correlation value and positive significance of both. This is seen at a correlation value of 0.704 while its significance value is 0.000. Thus, based on those numbers, the H0 hypothesis is rejected.